2017
DOI: 10.1002/hed.24798
|View full text |Cite
|
Sign up to set email alerts
|

Multiple single nucleotide polymorphism analysis and association of specific genotypes in FHIT, SAMD4A, and ANKRD17 in Indian patients with oral cancer

Abstract: Our study identified SNPs with susceptibility to oral cancer in high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The 260/280 ratio of the DNA was assessed and DNA quantified using NanoDrop 2000 Spectrophotometer (Thermo Fisher Scientific). Genotyping was performed using allelic discrimination Real‐Time PCR assay with SYBR Select Master Mix on a StepOne Plus Real‐Time PCR system (Applied Biosystems, CA) as previously described . Thirteen SNPs in seven transcription factor genes associated with proliferation, differentiation, and apoptosis were analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 260/280 ratio of the DNA was assessed and DNA quantified using NanoDrop 2000 Spectrophotometer (Thermo Fisher Scientific). Genotyping was performed using allelic discrimination Real‐Time PCR assay with SYBR Select Master Mix on a StepOne Plus Real‐Time PCR system (Applied Biosystems, CA) as previously described . Thirteen SNPs in seven transcription factor genes associated with proliferation, differentiation, and apoptosis were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Genotyping was performed using allelic discrimination Real-Time PCR assay with SYBR Select Master Mix on a StepOne Plus Real-Time PCR system (Applied Biosystems, CA) as previously described. 11,20 Thirteen SNPs in seven transcription factor genes associated with proliferation, differentiation, and apoptosis were analyzed. As a measure of quality control, 5% of samples were randomly selected and repeated with 100% concordance.…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol and smoked tobacco are the two key risk factors leading to oral cancer [ 76 , 77 ]. The researchers performed the single nucleotide polymorphism (SNP) analysis of rs1957358 in SAMD4A of 500 patients with oral cancer in India, and found that wild-type thymine (T) mutation to cytosine (C) significantly reduced the risk of oral cancer, such as rs1957358 TT mutation to rs1957358 TC, whereas rs1957358 TT reflected the increased risk [ 78 ]. This finding identifies SNPs with susceptibility to oral cancer in high risk populations and makes it possible to screen patients susceptible to oral cancer by SNP analysis.…”
Section: Samd4 and Related Diseasesmentioning
confidence: 99%
“…Studies from our group defined mutations and polymorphisms of biologically functional genes including oncogenes, tumor suppressor genes, apoptotic genes, receptor genes and signal transduction genes in oral cancer [10][11][12][13][14][15]. With advances in technology, high throughput microarray based whole genome expression analysis and whole genome association studies (GWAS), confirmed by nucleotide sequencing and allele specific oligonucleotide assays for examination of the genome, we identified several SNPs associated with increased or decreased risk of developing oral cancer [16][17][18][19][20][21][22]. Several global studies have highlighted the role of specific SNPs in oral cancer predisposition and oral cancer [17,[23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%